Effectiveness of fishbowl strategy on intermediate students’ achievement in geography subject (Journal Of Educational and Psychological Researches, 2017)
The aim of this study is to examine the effectiveness of fishbowl strategy as one of the effective learning strategies for intermediate students’ achievement in geography subject. To do this, three classes of second intermediate were chosen from Noor Al-Mustafa School for academic years (2015-2016). (64) Student were selected as a sample that distributed into two equal groups: experimental and control group. The research used the achievement test as an instrument to come up with the finding of the study. The experiment began on Tuesday 13th of October 2015 and ended on Tuesday 5th January 2016. Through this time, the researcher taught them the first and second chapter in geography of Arab homeland using fishbowl strategy for experimental group and traditional method for control group.  The author utilized T-test, Chi-square, and Pearson correlation coefficient to get the results. The result revealed that there are statistically significant differences at the level of (0, 05) between the mean scores of achievement test which went to experimental group.